Chemotherapy‐Induced Neuropathic Pain and Its Relation to Cluster Symptoms in Breast Cancer Patients Treated with Paclitaxel. Issue 1 (26th April 2012) - Golan‐Vered, Yael; Pud, Dorit
<x xml:space="preserve">Abstract</x> Abstract The majority of patients with breast cancer receiving chemotherapy report multiple symptoms. Compelling evidence has shown that subgroups of patients can be clustered by the severity of symptoms. Recent studies demonstrate that chemotherapy with such substances as paclitaxel can cause neuropathic pain (CINP) and consequently neural damage. Objectives: the present study examined the relationship between symptom clusters and CINP among 40 patients with breast cancer. The study was based on 2 sessions conducted before and during paclitaxel treatment. In each session, neuropathic pain was assessed by the DN4 Questionnaire. In the second session, the Lee Fatigue Scale, the General Sleep Disturbance Scale, and the Center for Epidemiological Studies–Depression Scale were also administered, and the worst pain intensity was assessed. Using cluster analysis, 2 symptom clusters were identified on the basis of the severity of the 4 symptoms scores. Patients in the High Cluster (37%) experienced a high level of all symptoms, whereas patients in the Low Cluster (63%) experienced a low level of all symptoms. Twenty patients (50%) were diagnosed with CINP. A subgroup of patients (23%) from the High Cluster was identified as having CINP; 35% were in the Low Cluster and free of CINP. In conclusion, there appears to be a specific subgroup of patients with hypersensitive cancer who need greater attention to symptom management. Early detection of symptoms, together with careful dose selection and assessment of early stages in the development of neuropathic pain, are essential for preventing the simultaneous occurrence of severe multiple symptoms and CINP.